Prevalence and availability of specialty dental care sites for children covered by Medicaid and CHIP in the United States - JonMichael Cope; Aaron David; Chase Otto; Inder Sehgal (Frontiers in Oral Health, 2026)
Introduction Access to dental care is a critical aspect of children's healthcare. For these reasons, Medicaid and Children's Health Insurance Program (CHIP), administered by states, cover medically necessary services. Specialty providers can enroll and participate in state or state-contracted plans, but availability varies widely. Our research objective was to evaluate the availability of non-general dentist specialists in endodontics, oral and maxillofacial surgery, orthodontics/dentofacial orthopedics on the InsureKidsNow website for Medicaid/CHIP enrollees, on a state-by-state basis, and to compare these with pediatric dental availability. Methods This is an observational, cross-sectional descriptive study. InsureKidsNow.gov was searched to identify and compare available and participating endodontists, oral and maxillofacial surgeons, and orthodontic/dentofacial orthopedic surgeons with pediatric dentists. The percentages of specialists listed on InsureKidsNow were compared with the respective percentages as a proportion of the state's dental workforce. A subanalysis of 25 states that listed a single plan was conducted to determine the patient-to-listed location ratio for each specialist category. For the largest benefit program, the combined percentage of the three specialties was graphed by state along with pediatric dentists. Data were grouped by whether they accepted new pediatric patients and by the total number of specialty locations. Results Children enrolled in Medicaid have very limited or no access to endodontists, oral and maxillofacial surgeons, or orthodontic/dentofacial orthopedic surgeons in half of the U.S. states. Thirteen states showed no availability of any non-primary care specialist for new participants, with the shortage being most pronounced for endodontic services. Among states using only one benefit plan, 12 of 25 showed no availability for new endodontic patients. In contrast to the non-primary care specialties, pediatric dentists were open to new patients in most states. Conclusions Despite improved use of dental services among children, those covered by public plans have limited access to one or more specialty provider types in most states. This limited access is most pronounced for endodontic services and may result from relatively low availability and/or participation of endodontic locations.